Global Perspectives on Health Promotion Effectiveness - McQueen, David V.; Jones, Catherine (Springer New York : Imprint: Springer, 2007)
As health improvement initiatives take center stage worldwide, public health professionals face an ongoing challenge to prove that the programs are worthwhile and that interventions make an impact. The Global Programme on Health Promotion Effectiveness (GPHPE) of the International Union for Health Promotion and Education takes on this challenge in Global Perspectives on Health Promotion Effectiveness. Fifty-five contributors representing six continents come together to analyze major programs around the world and evaluate their effectiveness. The result is a symposium in a book, the first in a series, representing the best critical thinking on crucial issues such as these: Assessment of evidence and evaluation of effectiveness in an international context. Synthesis of progress on the various GPHPE regional projects, with candid evaluations of strengths and limitations, and factors unique to each region. Advocacy to strengthen the evidence base for mental health promotion, physical activity promotion and a wide range of settings-based health promotion interventions. Challenges to health promotion and its assessment, including peace-building, urbanization, globalization, and social determinants. Global debates on emerging health promotion arenas-equity, methodology, partnership, development in adverse political climates, and others-as to whether or not traditional concepts of evidence, impact, and outcomes can be applied. Global Perspectives on Health Promotion Effectiveness is a significant document with profound implications for practitioners involved in implementing health promotion programs. It will serve as a vital source of frontline knowledge for researchers and students of public health.